The Influence of the Talented Generation Internship Program (Magenta) on Human Resource Management Readiness At the Port of Indonesia (Persero) I Medan - Hendra Utama; Mohammad Yusuf; Zulham Sitorus; Pebri Ramadani (Best Journal of Administration and Management, 2024)
PT Pelabuhan Indonesia (Persero) or Pelindo is a state-owned company which operates in the port services sector which provides opportunities for vocational/equivalent students, college students and fresh graduates to carry out internships in their environment. During the selection process, it was discovered that several of the interns accepted were interns who already had organizational experience. In carrying out an internship, interns not only help carry out supervisor/mentor duties, but interns are also helped to explore and improve their existing competencies so that they are better prepared to face the real world of work. This research aims to determine the influence of organizational experience and internship experience on work readiness of interns. This research uses quantitative research methods in the form of correlational research and explanatory research models, as well as collecting data through distributing questionnaires to interns at PT Pelabuhan Indonesia (Persero) I Medan. In processing the data, researchers used partial test methods and simultaneous tests for the variables organizational experience, internship experience, and work readiness with the help of SPSS version 26. The results of the study showed that organizational experience had a positive and significant effect on work readiness, internship experience had a positive and significant effect on work readiness, organizational experience and internship experience simultaneously influence work readiness